EXCISE TAX: STAGES OF REFORM IN UZBEKISTAN (International Journal of Economic Integration and Regional Competitiveness, 2024)
The article examines the economic essence, features, fiscal significance and stages of reforming the excise tax, and also develops proposals for improving the administration of the excise tax.